The development of the training course curriculum in indigenous vegetable production base on pesticide - free vegetable production system and local wisdom in agriculture for elderly - แก้วแดง กานต์ชัญญา (Community and Social Development Journal, 2017)
The purpose of this study was to develop and efficiency assessment of the training course curriculum in indigenous vegetable production base on pesticide - free vegetable production system and local wisdom in agriculture for elderly. 12 elderly in the area of Muang Khaen Municipality Maetang District, Chiang Mai Province. Data were collected by using and in-depth interview, group discussion and questionnaires. The training course curriculum prepared had efficiency of E1 / E2 according to the set criteria of 80 /80 , Mean, Standard deviation, paired t-test and content analysis were used for data analysis. The results found that pesticide-free vegetables product must provide body of knowledge, provide experience exchange activities and community rules on the concept of the agriculture of wisdom. The efficiency assessment of the training course curriculum were 81.48 / 89.56. Comparison of the training course curriculum the post – learning achievement score was higher than the pre – learning score at the 0.05 significant levels . In concluding, elderly suggested that to created the development of agriculture learning sources to occupation that is appropriate for their age.